2018
DOI: 10.1021/acsanm.8b00824
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Rich Brown TiO2–x Porous Flower Aggregates: Selective Photocatalytic Reversibility for Organic Dye Degradation

Abstract: A low-temperature, Mn(II)-assisted sol-solvothermal strategy has been developed for the synthesis of positively surface-charged defective brown TiO 2−x flower aggregates with porous nature. The porous structure possessed enormous surface defect states such as trivalent titanium ion (Ti 3+ ) and oxygen vacancy (V o ) sites. The defect states present in the brown TiO 2−x facilitated enhanced absorption even in the NIR region of the solar spectrum, whereas for the negatively surface-charged TiO 2 sample, synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…8 Schematic "phase diagram" that illustrates the visual color of the synthesized TiO 2 powders, the predominant form of nitrogen doping, and the TiO 2 particle microstructure as a function of the electrode position relative to the oxygen inlet and of the plasma power commercial P25 powder. Both MO and MB dyes are common for benchmarking the photocatalytic of TiO 2 [2,45,48,51,56,60,[78][79][80]. While we do not expect our materials to outperform P25, which is widely seen as gold standard for photocatalytic activity, the intent of this study is to understand how the tunable properties of our materials translate into tunable photocatalytic performance.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…8 Schematic "phase diagram" that illustrates the visual color of the synthesized TiO 2 powders, the predominant form of nitrogen doping, and the TiO 2 particle microstructure as a function of the electrode position relative to the oxygen inlet and of the plasma power commercial P25 powder. Both MO and MB dyes are common for benchmarking the photocatalytic of TiO 2 [2,45,48,51,56,60,[78][79][80]. While we do not expect our materials to outperform P25, which is widely seen as gold standard for photocatalytic activity, the intent of this study is to understand how the tunable properties of our materials translate into tunable photocatalytic performance.…”
Section: Resultsmentioning
confidence: 96%
“…Prior research on photocatalytic degradation of MB and MO of similar concentration (10 −4 M) revealed that typically a catalyst concentration of around 0.5 g/L is required to reach an efficient degradation of 70-90% within 120-240 min [45,79]. Furthermore, additional supplements such as the addition of H 2 O 2 or metal ion doping are usually used to enhance radical production or adjust surface charges in order to degrade different types of organic dyes [45,46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Followed by that, blue [ 151 ], brown [ 152 ], and red titania [ 153 ] were reported. Ullattil et al reported low-temperature synthesis of defective brown titania porous flower aggregates using Mn(II) as reducing agent and template for broad and longer wavelength absorbing material via sol-solvothermal process [ 154 ]. The synthesized brown titania had flower like aggregates that contains ample defects states where titania was found as trivalent ion and oxygen vacancies.…”
Section: Applications Of Titania As Photocatalystmentioning
confidence: 99%